Development of Comic-Based Learning for Maharah Qira’ah Using Canva in Madrasah Tsanawiyah Shirothul Fuqoha’ Malang - Alvina, Vikria Tahta; Yakin, Haqqul; Hilmi, Danial; Basid, Abdul (Borneo Journal of Language and Education, 2025)
The lack of prior knowledge among the students and the tedious lecture-based teaching techniques provide difficulties for Arabic reading education at MTs Shirothul Fuqoha' Malang. In order to improve maharah qira'ah through an interactive method, comic-based educational resources were created using Canva. The objectives of this study were to describe the creative process, ascertain viability, and evaluate efficacy. The study included 53 eighth-grade students who were split into two groups: experimental (25) and control (28) participants. Observation, interviews, surveys, and tests were used to gather data, which SPSS 25 was then used to evaluate for validity, reliability, normalcy, and T-tests. The requirements analysis was the first of 10 steps in the media development process. The instructional medium received a good rating of 96%, while the content and language received an 86% rating from expert validation. The final media was created following experiments and adjustments. According to the findings, the experimental group's post-test score (83.33) was 11.73 points higher on average than the control group's (71.60). With a significant value of 0.000, the Independent Sample T-Test verified the effectiveness of the media in improving maharah qira'ah at MTs Shirothul Fuqoha' Malang.